(untitled) (Latakia University Journal -Basic Sciences Series, 2018)
إن استخدام الثنائيات (الديودات) من نوع GaAs (p-i-n) ككواشف للفوتونات عالية الطاقة تقتضي زيادة سماكة منطقة الفراغ W حيث توجد الشحنة، وتلك المنطقة تحدد بالشوائب المتبقية لنصف الناقل. سوف نتحدث عن التقانة المستخدمة في زيادة سماكة منطقة الشحنة الفراغية W. ويقتضي هذا تعديل الشوائب المتبقية بتشكل عيوب عن طريق التشعيع بالإلكترونات. تمت دراسة التيار والسعة بتابعية الجهد المطبق على الكاشف GaAs (p-i-n). توضح النتائج التي حصلنا عليها حدود التقنية المستخدمة في حالة هذا النوع من الكواشف. The detection of high-energy photons, using compound semiconductor detectors such as GaAs (p-i-n), requires an increase of the depleted zone W, which is limited by the residual doping of the semiconductor. In this paper, we will discuss a technique by which the extension of the space charge region of a diode can be increased. It consists in compensating the residual doping impurities with defects introduced by electrons irradiation. We have studied the current and capacitance-voltage characteristics of GaAs (p-i-n) structures. Results are presented to illustrate and evaluate the limits of this technique in the case of GaAs (p-i-n) structures.